The Influence of Product Quality, Brand Image, and Price on Purchase Decision at CV Sarana Berkat Pekanbaru - Ivan Reinaldo; Stefani Chandra (Journal of Applied Business and Technology, 2020)
Lately the development and competition of cosmetic market is getting tighter, especially in the hand & body lotion sector. The increasing number of both imported and local products in Indonesian market has urged the local cosmetic companies to repeatedly come up with new strategies and innovations to attract consumers. One of them is by focusing on product quality, brand image, and price to influence consumers’ purchasing decisions. This research aims to determine the effect of product quality, brand image, and price on purchasing decisions of Aulia hand & body lotion at CV Sarana Berkat Pekanbaru. The data used was primary data which was obtained through questionnaires and processed using SPSS 21.0. The total sample in this research consisted of 150 respondents which were selected using accidental sampling. The data analysis technique used was multiple linear regression. The result showed that product quality, brand image, and price have positive influence on purchasing decision.